IGF-1 Levels Among Adolescent Girls Living In Jakarta and It's relation to Nutritional Status - Maretha Primariayu; Ririn Hariani; Saptawati Bardosono; Noorwati Sutandyo (World Nutrition Journal, 2018)
Background and Objective:Insulin-like growth factor (IGF)-1 is one of the hormones that plays a role in the growth of adolescent girls. Its level will rise at puberty and begin to decline at the end of puberty. High IGF-1 levels in adult is associated with the incidence of breast cancer. This study aims to know the level of IGF-1 and investigates its relationship with dietary intake, nutritional status, and physical activity of adolescent girls aged 13-15 in Jakarta.Methods and Study Design:This cross-sectional study used secondary data from a previous study (titled "Determinant Factor Levels of Estradiol, IGF-1, and Early Menarche in Adolescent Girls Aged 13-15 in Jakarta: Nutritional Epidemiology Study Related to Breast Cancer Risk Factors") and primary data from stored blood serum to measure IGF-1 levels by colorimetric method. The secondary data such as dietary intake, anthropometric data, and physical activities were obtained from 178 subjects with a total population sampling method.Results and Conclusions:There was a positive correlation between IGF-1 levels and carbohydrate intake (p=0.041, r=0.153) and a negative correlation between IGF-1 levels and fat intake (p=0.042, r=-0.152). No correlation between IGF-1 and body mass index was found, but there was a tendency that IGF-1 values would increase in overweight and decrease in obesity. IGF-1 levels have nonlinear pattern by carbohydrates intake, fat intake and nutritional status. In conclusion, the adolescent girls should maintain their nutritional status by maintaining diet, choosing the right and balanced foods, as well as increasing physical activities.